VOCABULARY LEARNING STRATEGIES OF EFL STUDENTS AT TERTIARY LEVEL - Achmad Yudi Wahyudin; Reza Pustika; Marta Widiawitasari Br Simamora (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2021)
This article aims at investigating the vocabulary learning strategies of EFL learners at tertiary level. Since the students are required to pass English as a required subject in Indonesian tertiary education, exploring vocabulary strategies attracts more attention from teachers and practitioners. A survey approach was carried out in conducting this research. The present study involved 120 non-English major participants to fill out a questionnaire consisting of four vocabulary learning strategies: cognitive, metacognitive, memory, and determination strategies. The data of this research were descriptively analysed to reveal the vocabulary learning strategies used by EFL learners at tertiary level. This study reveals that the cognitive strategy is the most frequently strategy used. The respondents use new words in a sentence to remember them from time to time. While the least frequently strategy used is making a mental image to remember the words. The findings of the study might give an insight for English as a foreign language (EFL) teachers and practitioners to consider changes and adjustments to their pedagogical practice.